Phasing Out Subsidies : Recent Experiences with Fuel in Developing Countries - Bacon, Robert; Kojima, Masami (World Bank, Washington, DC, 2012)
Many developing countries subsidize petroleum products. The doubling of world oil prices since January 2004 has had very high fiscal costs for these countries, increasing public debt and squeezing other government spending. The subsidies have also had unintended results. But phasing out subsidies is politically challenging. This paper reviews some successful strategies for removing or reducing subsidies while protecting the poorest consumers.